Individual differences in approach-avoidance aptitude: some clues from research on Parkinson’s disease - Costa, Alberto; Caltagirone, Carlo (Frontiers in Systems Neuroscience, 2015)
Approach and avoidance are two basic behavioral aptitudes of humans whose correct balance is critical for successful adaptation to the environment. As the expression of approach and avoidance tendencies may differ significantly between healthy individuals, different psychobiological factors have been posited to account for such variability. In this regard, two main issues are still open that refers to i) the role played by dopamine neurotransmission and ii) the possible influence of cognitive characteristics, particularly executive functioning. The aim of the present paper was to highlight the contribution of research on Parkinson’s disease (PD) to our understanding of the above issues. In particular, we here reviewed PD literature to clarify whether neurobiological and neuropsychological modifications due to PD are associated to changes in approach-avoidance related personality features. Available data indicate that PD patients may show and approach-avoidance imbalance as documented by lower novelty-seeking and higher harm-avoidance behaviors, possibly suggesting a relationship with neurobiological and neurocognitive PD-related changes. However, the literature that directly investigated this issue is still sparse and much more work is needed to better clarify it.